2004
DOI: 10.1002/bem.20010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human EEG caused by low level modulated microwave stimulation

Abstract: This study focuses on the effect of low level microwave radiation on human EEG alpha and theta rhythms. During the experiment, 20 healthy volunteers were exposed to a 450 MHz microwaves with 7 Hz on-off modulation. The field power density at the scalp was 0.16 mW/cm2. Signals from the following EEG channels were used: FP1, FP2, P3, P4, T3, T4, O1, and O2. The experimental protocol consisted of one cycle of short term photic and ten cycles of the repetitive microwave stimulation. The changes caused by photic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 21 publications
2
46
1
1
Order By: Relevance
“…Following this rationale, the EMF, as a nonspecific weak physical stressor, would not affect brain activity during a short stimulation period, but it would during repetitive stimulations and longer interaction times. In agreement with Hinrikus, we wish to stress that ''the influence of on-off stimulation cycles on the human brain activity can be different from continuous exposure by a modulated microwave'' [see Vorobyov et al, 1997;Hinrikus et al, 2004 for similar results].…”
Section: Discussion and Perspectivesmentioning
confidence: 63%
See 1 more Smart Citation
“…Following this rationale, the EMF, as a nonspecific weak physical stressor, would not affect brain activity during a short stimulation period, but it would during repetitive stimulations and longer interaction times. In agreement with Hinrikus, we wish to stress that ''the influence of on-off stimulation cycles on the human brain activity can be different from continuous exposure by a modulated microwave'' [see Vorobyov et al, 1997;Hinrikus et al, 2004 for similar results].…”
Section: Discussion and Perspectivesmentioning
confidence: 63%
“…Indeed, a small change in one part of the EEG track does not provide a noticeable change in the energy of the whole track recording. According to Hinrikus et al [2004], nonlinear EEG signal processing methods, which are capable of detecting differences in the character of the signals, might be helpful in the detection of specific changes.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Microwave exposure at the non-thermal level of field power density was selected identical to that in our previous studies except modulation frequencies (Lass et al 2002;Hinrikus et al 2004Hinrikus et al , 2005Bachmann et al 2004;Bachmann et al 2005a). Exposure conditions were the same for all subjects.…”
Section: Microwave Exposurementioning
confidence: 99%
“…However, the effect is weak and difficult-to-detect. Several investigators have reported that low-level exposure produces alterations in the EEG signal and brain behavior (Mann and Roschke 1996;Borbely et al 1999;Huber et al 2000;Lass et al 2002;Hinrikus et al 2004;Curcio et al 2005), while others conclude that exposure to electromagnetic field does not alter resting EEG (Hietanen et al 2000;. Reports of possible non-thermal EMF effects are often contradictory and the difficulties in independent repeating of the experimental results cause doubts.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying the effects of exposure at low and high frequency EMF are different, thus we can not propose in this case a possible mechanism of interaction based on Larmor precession theory as previously done. However, effects of exposure to microwaves at 0.450 GHz with 7 Hz on-off modulation on EEG alpha rhythms in human brain have been also reported [Hinrikus et al, 2004]. Because of the pulsed nature of the FEL, it was not possible to make a rigorous comparison between CW and pulsed irradiation at 130 GHz.…”
Section: Discussionmentioning
confidence: 94%